Fast and accurate dynamic synchrophasor estimator for protection applications. (10th May 2021) - Khettaoui, Billal; Boudour, Mohamed
This paper proposes a new synchrophasor estimation algorithm capable of speeding up the rate of measurements. It reduces the computational complexity and meets the accuracy requirements of the P-class phasor measurement unit (PMU) defined by the IEEE Std C37.118.1™-2011 and its amendment IEEE Std C37.118.1a™-2014. The proposed estimator is constructed by inserting the second order Taylor polynomial of signal model in the modulated sliding discrete Fourier transform (MSDFT) expression, taking advantage of the dynamic model of the Taylor series expansion and the low computational complexity of the MSDFT. The proposed technique is found to be as accurate as the traditional one (based on joint application of Taylor's second order polynomial and the DFT) with higher reporting rates and it satisfies all the tests listed by the standard as well as the influence of wideband noise and decaying DC component.